2020
DOI: 10.1128/msystems.00433-20
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in a Whitefly Vector Activated by a Begomovirus Enhances Viral Transmission

Abstract: Apoptosis is generally considered the first line of defense against viral infection. However, the role of apoptosis in the interactions between plant viruses and their insect vectors has rarely been investigated. By studying plant DNA viruses of the genus Begomovirus within the family Geminiviridae, which are transmitted by whiteflies of the Bemisia tabaci species complex in a persistent manner, we revealed that virus-induced apoptosis in insect vectors can facilitate viral accumulation and transmission. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 43 publications
1
30
0
1
Order By: Relevance
“…Begomoviral proteins have been characterized for understanding the mechanism of symptom recovery [ 61 , 62 ], virulence, and host resistance [ 63 , 64 ]. Coat protein (CP) is a multifunctional protein due to its interaction with plants and vectors [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Begomoviral proteins have been characterized for understanding the mechanism of symptom recovery [ 61 , 62 ], virulence, and host resistance [ 63 , 64 ]. Coat protein (CP) is a multifunctional protein due to its interaction with plants and vectors [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that apoptosis enhanced TYLCV loading while autophagy eliminated in MEAM1 whitefly (Wang et al, 2016; Wang et al, 2020c), but is still unclear whether simultaneous activation of apoptosis and autophagy was essential in MED whitefly for co-existence with TYLCV. We therefore introduced a serial of pharmacological experiments to artificially regulate the apoptosis and autophagy of whitefly, and to determine effects of these PCD on virus loading.…”
Section: Resultsmentioning
confidence: 99%
“…Although TYLCV could also induce PCD in MEAM1 species, the most striking difference is the initiation timepoint of PCD after acquiring TYLCV. Specifically, MED whitefly needs 6-12 hours to initiate PCD while MEAM1 needs a relative longer time from 24 to 48 hours (Wang et al, 2016; Wang et al, 2020c). Considering PCD could be essential for virus acquisition, PEBP4-dependent PCD in MED species has quicker initiation than PEBP4-independent PCD in MEAM1 species, possibly resulting in higher virus capacity for MED species (Kliot et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations